QUALITY OF LIFE IN BRONCHIAL ASTHMA - Ikramova Aziza Shakirovna; Djabbarova Aqida Mannapovna; Hamraeva Nasiba Abdurasulovna (Journals Park Publishing, 2023)
The quality of life indicators were studied in 62 patients with moderate and severe bronchial asthma who were admitted to inpatient treatment due to an exacerbation of the disease. The survey was conducted using special AQLQ questionnaires and SGRQ on the 2nd-3rd day of the examination and after the initial treatment. A significant decrease in quality of life indicators was revealed in patients with bronchial asthma during the period of exacerbation of the disease. In patients with severe bronchial asthma, compared with patients with moderate bronchial asthma, more low values of quality of life. After the treatment, the quality of life indicators increased significantly, but remained lower than in patients with moderate bronchial asthma. At the end of hospitalization, there is an inverse correlation between the duration of the disease and the quality of life scales. In addition to reducing the symptoms of the disease and the positive dynamics of lung function indicators, achieving remission of bronchial asthma is accompanied by a significant improvement in the quality of life of patients.
Keywords: bronchial asthma, quality of life.